Effect of different energy and protein levels on growth performances and carcass yields of Sonali chicken (Bangladesh Journal of Animal Science, 2024)
This study evaluated how varied energy and protein levels affect the growth and carcass traits of Sonali chickens. A 63-day experiment was conducted on 400-day-old Sonali chicks that were raised straight. The chicks were split into four groups of 100 birds apiece, which were then further separated into four subgroups of 25 birds each. The treatment groups were: T1 (2900 kcal/kg ME, 20% CP for starter and 3000 kcal/kg ME, 19% CP for grower); T2 (2900 kcal/kg ME, 21% CP for starter and 3000 kcal/kg ME, 20% CP for grower); T3 (2950 kcal/kg ME, 20% CP for starter and 3050 kcal/kg ME, 19% CP for grower) and T4 (2950 kcal/kg ME, 21% CP for starter and 3050 kcal/kg ME, 20% CP for grower) group. Sonali chicks were fed on starter diets from day old to 5 weeks of age and grower diets from 6 to 9 weeks of age. Results revealed that body weight was significantly (P